Gender stereotyping: Evidence from gender differentiated household vulnerability to climate change in Eastern Uganda - Balikoowa, Kenneth; Nabanoga, Gorettie; Tumusiime, David. M. (Cogent Environmental Science, 2018)
A narrative linking women and vulnerability has been overarching in vulnerability literature. However, this narrative has not been empirically proven aside from generalizations based on poverty-gender linkages. This study used primary data collected in 2016 from 735 randomly selected households in Eastern Uganda to construct a gender vulnerability index based on the livelihood vulnerability framework to determine the most vulnerable gender differentiated households. The results showed that single male-headed households were the most vulnerable to climate change, even worse than single female-headed households. Mixed gender households showed lowest vulnerability. Presence of a female spouse reduced the vulnerability of the traditionally “male headed” households. The results suggest that disparity in access to requisite resources mediates vulnerability among groups of households. It is concluded that the straight assumption that vulnerability is associated with female-headed households is misleading and could disenfranchise some male-headed households that are more vulnerable.
Keywords: Vulnerability; Adaptive capacity; Gender; Climate change